When a Church becomes a Mosque: The former Kapernaumkirche in Hamburg - Pettersson, Maria Grazia (Chrześcijaństwo-Świat-Polityka, 2025)
In most European states, a different legal order applies to the majority church as to religious minorities. Most European states and international law provide legal protection for religious minorities, either within the framework of religious freedom [e.g. art. 18 UDHR] or by specific legislation for numerical minorities [e.g. Capotorti 1979]. This article examines the case of the former Protestant Kapernaumkirche in Hamburg which has been turned into a mosque in order to show what individualisation theory [e.g. Davie 1994; Heelas, Woodhead 2005; Hervieu-Léger 1999, 2000; Cipriani 1999, Knoblauch 1999] can contribute to understand current developments in Europe’s religious landscape, and for assessing the appropriateness of the current legal order for a situation where Christians constitute the numerical majority in Germany, but show low church attendance and decreasing religious belief [Pickel 2018]. Since the church is classified as a monument, even the legal framework of law on monument protection is considered.